Can Homeopathy, a Particularly Mild Therapeutic Approach, Survive and Grow in a World of Violence? - Vithoulkas, George (Homeopathy, 2020)
This short treatise addresses a philosophical question concerning the place of homeopathy in our modern world. The question raised is whether a therapeutic system as peaceful, mild, and non-violent as homeopathy can survive and grow within a society that often displays the opposite characteristics.Much of contemporary society is more interested in fast and impressive cures, even if these may also bring side effects; whereas homeopathy can offer solutions with a personalized approach that requires long hours of case study by the homeopath to find the correct personal remedy that aims to bring about positive results, which the therapy can produce in deep chronic diseases.The conclusion drawn is that homeopathy does not readily fit within a modern and violent society that prefers quick and invasive solutions to its clinical problems.
Keywords: homeopathy; society; violence; aggression; personalized treatment